English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

im having trouble with this problem use substition method and explain...
2x + y = 5
x - y = 4

2006-09-10 07:24:26 · 11 answers · asked by katie w 1 in Science & Mathematics Mathematics

11 answers

2x + y = 5
x - y = 4

you need to remove 'y' or ' x ' its up to u . but you should find that one is easier.

here you can remove y b coz you have -y & +y , so we have;
2x + y = 5
x - y = 4;
(2x + x) + (+y - y) = 5 + 4
3x = 9
x = 9/3 ; x = 3
her you can find y ;
if x = 3 ; x - y = 4 ; 3 - y = 4 ; -y = 4 - 3 ; -y = 1 , y = -1

so x = 3, y = -1
(+3 , -1)

Good Luck darling.

2006-09-10 09:24:38 · answer #1 · answered by sweetie 5 · 0 0

What you need to do is rearrange one equation, so that all you have is ONE variable on one side.

2x + y = 5 can be rearranged into:
1) Y = 5 - 2x
2) X = (5 - y)/2

x - y = 4 can be rearranged into:
1) Y = x - 4
2) X = y + 4

Take any one of these equations and replace the X or Y with the statement on the right side of the '='

For example:
2x + y = 5 becomes 2(y+4) + y = 5, because you substitute (y+4) into where the X was.

Once you have an equation with only one variable, be it Y or X, you can solve for an actually value. Plug THAT value back into the equation, and you can solve for the OTHER variables value.

2006-09-10 07:33:07 · answer #2 · answered by Matt 2 · 0 0

Ok, you've got 2 equations

2x + y = 5 and x - y = 4. Using the subsitution method, you want to have one of the unkowns (x or y) on one side of the equation, usually on the left side. Once that's done you can subsitute that expression for x or y in the other equation.

In your example, use the 2nd equation

x -y = 4

Isolate x by adding +y to both sides of the equation which gives you

x - y + y = 4 + y or x = 4 + y

Now you've the got the 2nd equation as expression of x, x = 4 + y,

Take this expression and SUBSTITUTE it in the first equation.

2x + y = 5

2(4+y) + y = 5

Now 'foil' and solve for y and x..

8+ 2y+y = 5
3y+ 8 = 5
3y = -3
y = -1

Use the x - y = 4 to solve for x

x - (-1) = 4
x +1 = 4
x = 3

Hope that helps

2006-09-10 07:34:34 · answer #3 · answered by Mark B 2 · 0 0

2x + y = 5
x - y = 4

Solve one of the equations for a variable (usually the "easier" one):
x - y = 4 should be -y = 4 - x, or to get y positive, multiply through the equation by -1, so you'd end up with:

y = -4 + x (which is the same as y = x - 4). So take that and put it in for y:

2x + y = 5
2x + (x - 4) = 5.......and then solve for x first:

2x + x - 4 = 5.......substitute (x - 4) for y
3x - 4 = 5.............combine like terms
3x = 9..................solve for x.
x = 3

Then go back to the original equation and put x in to find y:
2x + y = 5
2(3) + y = 5.......subsitute your answer for x
6 + y = 5...........simplify & solve for y
y = -1

Then to check:

2x + y = 5
2(3) + (-1) = 5
6 + -1 = 5 so it checks!

2006-09-10 07:38:44 · answer #4 · answered by Anonymous · 0 0

3x + 6y = 30 (equation a million) 1x + 6y = 20 (equation 2) Subtract equation 2 from equation a million: (3 - a million) x = 30 - 20 2x = 10 x = 10/2 = 5 substitute x in equation 2 with its fee 5 + 6y = 20 6y = 20 - 5 = 15 y = 15/6 = 5/2 The pair of strategies to those simultaneous equations is (5, 5/2)

2016-12-18 08:05:15 · answer #5 · answered by gerrit 4 · 0 0

Isolate either x or y for either equation and then substitute for x if x was isolated, or y if y was isolated into the other equation.

Say (1) 2x + y = 5 (2) x-y=4

(2)x=4 + y where has been isolated in equation 2

substiture into equation (1)-------------

2(4 +y) + y = 5

8+ 2y +y =5

3y=-3

y=-1----------------------now put y value back into the isolated original isolated x usage equation---------x= y +4----------x= -1 + 4= +3

or

using equation (1) isolate y where:

2x + y = 5

y= -2x + 5----------substide into y in equation (2)

x - y = 4

x - (-2x + 5)=4

x + 2x -5 =4

3x=9---------------as such x=+3 and now put x value back into the isolated original y isolated usage equation----------------

y= -2x +5 = -2(+3) +5= -6 +5 =-1


both methods work either you isolate y or x in either equation 1 or 2, any none works.

2006-09-10 07:39:02 · answer #6 · answered by Zidane 3 · 0 0

Substitution means to express one variable with the other. Most people don't like fraction or negative coefficient, so I recommend you work on the second equation:

x=y+4

substitute x in the first equation with y+4:

2(y+4)+y=5,
3y+8=5
3y=-3
y=-1

therefore x=y+4=-1+4=3

So the solution of this linear system is:(3,-1), or x=3, y=-1

2006-09-10 07:27:00 · answer #7 · answered by Hex 2 · 0 0

first change the 2nd equation to x=4+y
then substitute it into the first equation like this:

2(4+y) + y = 5
8 +2y +y = 5
8 + 3y =5
-8 -8
3y = -3
divide by 3
y = -1

then substitute -1 into the second equation for y

x - (-1) = 4
x + 1 = 4
- 1 -1
x = 3

2006-09-10 15:34:30 · answer #8 · answered by tejones1227 1 · 0 0

In this case, the ys cancel out (-y + y = 0)

So you're left with

3x=9

x=3

Plug it into equation 2 - I picked this one because you don't have to multiply. I prefer to deal with smaller numbers.

3 - y = 4

y + 4 = 3

y = -1

(3, -1)

2006-09-10 09:10:16 · answer #9 · answered by themacncheesepunk 3 · 0 0

2x + y = 5
x - y = 4

x - y = 4
x = y + 4

2(y + 4) + y = 5
2y + 8 + y = 5
3y + 8 = 5
3y = -3
y = -1

x = -1 + 4
x = 3

ANS : (3,-1)

2006-09-10 13:20:25 · answer #10 · answered by Sherman81 6 · 0 0

fedest.com, questions and answers